PENYALAHGUNAAN NARKOBA DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Ahmad Syafi'i (State Institute of Islamic Studies (IAIN) Palu, 2009)
In Indonesia, the penal issues of psychotropic drugs can be described from two aspects: types of psychotropic drugs which have been abused and types of drug abuse which have their own different penalties. A judge in his or her interpretation of this issue just looks at the maximum amount, not minimum one. In the perspective of Islamic law, some moslem scholars make an analogy of these kinds of drug to khamr (wine) because of the same reason (‘illat, ratio legis); that is, intoxication. Concerning to the penalty to drug abusers, some moslem scholars argued that the penalties are had, while others said ta’zîr as a maximum punishment to this crime, and it is within the authority of the moslem judges.Kata Kunci: penyalahgunaan narkoba, hukum positif, hukum Islam